The Model Determination Of Buffer Of Systemic Strategic Risk Of Borrower For Hedging Force Major Circumstances - Anatolievna, BurdinaAnna; Victorovna, BondarenkoAnna (The journal of contemporary issues in business and government, 2021)
The study substantiates the concept of systemic strategic risk of borrower and buffer of systemic strategic risk of borrower for hedging force major circumstances in order to improve monetary policy. There is analysis of rules and regulations for the analysis of credit risk of bank. The authors studied the existing approaches to assessing the creditworthiness of borrowers and the credit risk of a bank. The factors, which influence on the level of credit risk of borrower, are identified. Quantitative and qualitative parameters of borrower's creditworthiness, used in banking risk management, are determined. An economic and mathematical model is proposed for determining the systemic strategic risk buffer of borrower for force major circumstances hedging. Considering the level of losses during default, the probability of default of borrower and strategic risk. It is proposed to use the developed technology for creating a systemic strategic risk buffer for borrower for force major circumstances hedging as a monetary policy tool and include Basel III in the requirements of the banking agreement.